The Influence of Tertiary Education Disciplines on Self-Construals and Conflict Management Tendencies - Wee, Sheila X. R.; Choo, Wan Yee; Cheng, Chi-Ying (Frontiers in Psychology, 2021)
While cultural difference on self-construal are well-documented, how acculturation to a new cultural environment could change an individual’s self-construal remains under-explored. In this research, how tertiary education disciplines could be associated with the endorsement of self-construals which, in turn, affect students’ conflict management tendencies were explored. Study 1 revealed that across the U.S. and Singapore, college students from business and social science disciplines exhibited the trend of endorsing more independent and interdependent self-construal respectively, regardless of the different dominant self-construals in the two countries. Study 2 explored how tertiary education disciplines is associated with individuals’ conflict management tendencies via the endorsement of different self-construals among Singaporeans. Findings showed that individuals from business discipline possess a more independent self-construal and in turn endorsed more of a competing conflict management style than those from social sciences. Different disciplinary cultures could link to conflict management tendencies via the endorsement of self-construals, yielding significant theoretical and practical implications